2009
DOI: 10.1016/j.jjcc.2008.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Peak time of acute coronary syndrome in patients with sleep disordered breathing

Abstract: The results of this study suggest a possible relationship between SDB and the onset of ACS between midnight to morning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…However, the rate of sleep apnea we found in our subsample may be an overestimation because those undergoing PSG had a somewhat higher BMI (33.6 ± 6.8) versus those who did not (30.6 ± 7.2). Nonetheless, others have previously reported a high prevalence of sleep apnea in ACS patients before discharge 3 days 46) and 2-3 weeks 47) after the acute event. Sleep apnea has significant negative effects on quality of life and also predicts in-hospital recurrent cardiac events in ACS patients.…”
Section: Discussionmentioning
confidence: 90%
“…However, the rate of sleep apnea we found in our subsample may be an overestimation because those undergoing PSG had a somewhat higher BMI (33.6 ± 6.8) versus those who did not (30.6 ± 7.2). Nonetheless, others have previously reported a high prevalence of sleep apnea in ACS patients before discharge 3 days 46) and 2-3 weeks 47) after the acute event. Sleep apnea has significant negative effects on quality of life and also predicts in-hospital recurrent cardiac events in ACS patients.…”
Section: Discussionmentioning
confidence: 90%
“…The prevalence of OSA is 2-to 3-fold higher in patients with a history of myocardial infarction (MI). 95 Recent studies have also reported that the odds of having OSA in patients with nocturnal onset of MI was 6-fold higher than in those with MI onset during the daytime, suggesting that OSA leads to an increased risk of MI during the night 96,97 (Figure 4). Patients who suffer from ischemic heart disease and OSA may be at a higher risk for STsegment depression during sleep.…”
Section: Cadmentioning
confidence: 99%
“…Patients with SDB are more likely to have cardiac events during nocturnal hours [30]. Acute coronary syndromes (ACS) are more frequent during night time in OSA patients as opposed to the well-documented diurnal pattern of presentation in the general population [31].…”
Section: Ischaemic Heart Diseasementioning
confidence: 99%